Sprachen und Bildungspolitik in Algerien - Yamina, Hamida (Stellenbosch Papers in Linguistics Plus, 2012)
Abstract:Languages like German, Spanish and Italian that are taught at tertiary education institutions, currentlyhave become more significant in Algeria than is generally assumed. The continuing expansion of theselanguages at tertiary level will gradually contribute to a resolution in the battle for status betweenFrench and English in language planning debates. This paper considers which parties currently opposeFrench and promote English as the first foreign language (FL1), what the reasons are for attempting toestablish English as FL1 at primary schools, why such an endeavour is doomed from the onset, andhow an FL3, like German, may benefit from this state of affairs. Attached to this, the status ofindigenous lanuages, like Algerian and Berber are considered in the complex plurilinguisticenvironment where “arabicization” is an issue. The paper topicalises linguistic and didacticconsequences of such considerations, specifically concerning plurilingualism at primary school leveland in academia.Keywords: Algeria, education policy, language conflict, mother tongue, second language, foreignlanguageSchlüsselbegriffe: Algerien, Bildungspolitik, Sprachkonflikt, Muttersprache, Zweitsprache,Fremdsprache